Hacking Ético a dispositivos móviles android por playload, año 2024 - Remache Pérez, Kleber Alberto (2025)
This research project explores in Android mobile devices through Ethical Hacking and the use of playload malicious loads designed to exploit security flaws. Background research highlights Android’s dominance, holding a 76% global market share, and its exposure to threats, worsened by version fragmentation and user unawareness, which enable attacks such as those previously identified involving malware and excessive app permissions. The main objective is to describe these vulnerabilities in a controlled environment, utilizing tools like MSFVenom to create APK playload and Metasploit Framework to simulate intrusions. By implementing a descriptive research with a qualitative and quantitative approach, the study documents security gaps exploited via social engineering or malicious APK execution, revealing how cybercriminals extract sensitive data, such as contacts or geolocation. The results, obtained from tests on several Android mobile devices, rank vulnerabilities according to their likelihood of exploitation (low, medium, high) and impact (minor, moderate, catastrophic), identifying high-risk commands like "dump_sms" and "geolocate." These findings underscore the ease of unauthorized access and emphasize the need for system updates and user awareness. In conclusion, Ethical Hacking with playload provides insights into Android’s weaknesses, offering a framework to mitigate risks in a widely popular system that faces significant challenges from malicious actors, particularly when only 40% of users regularly update their devices.